2015
DOI: 10.1364/boe.6.000987
|View full text |Cite
|
Sign up to set email alerts
|

Technique for real-time tissue characterization based on scanning multispectral fluorescence lifetime spectroscopy (ms-TRFS)

Abstract: Abstract:We report a novel technique for continuous acquisition, processing and display of fluorescence lifetimes enabling real-time tissue diagnosis through a single hand held or biopsy fiber-optic probe. A scanning multispectral time-resolved fluorescence spectroscopy (ms-TRFS) with self-adjustable photon detection range was developed to account for the dynamic changes of fluorescence intensity typically encountered in clinical application. A fast algorithm was implemented in the ms-TRFS software platform, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…19 Multimodal instrumentation combining FLIm and ultrasound has also been used to monitor matrix composition and mechanical properties of engineered cartilage tissue during maturation. 20,21 Recent advantages in FLIm devices using miniature fiber optics probes, along with fast electronics enabling fast data acquisition speed, analysis, and real-time display 22 make this technique highly compatible with modern clinical arthroscopes. Hence, the goal of the present study was to investigate the feasibility of using FLIm for early detection of cartilage disease.…”
Section: Introductionmentioning
confidence: 99%
“…19 Multimodal instrumentation combining FLIm and ultrasound has also been used to monitor matrix composition and mechanical properties of engineered cartilage tissue during maturation. 20,21 Recent advantages in FLIm devices using miniature fiber optics probes, along with fast electronics enabling fast data acquisition speed, analysis, and real-time display 22 make this technique highly compatible with modern clinical arthroscopes. Hence, the goal of the present study was to investigate the feasibility of using FLIm for early detection of cartilage disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has explored the application of fluorescence lifetime imaging (FLIm) for oral carcinoma detection [9], atherosclerotic plaque assessment [10] and characterization of engineered tissues [11]. More recently we have also reported the ability to measure lifetime from tissue and to augment white-light video frames in real-time [12, 13]. Quantification of emission spectrum and lifetime is performed through different analysis tools.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [9, 28], we showed that the area over which fluorescence signals are measured is approximately equal to the size of the fiber core, when the probe-to-target distances are smaller than 3 mm. As expected, though, in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although scanning techniques have shown potential to provide real-time feedback about the biochemical features of tissue at each measured location [6–10], their clinical implementation is still limited by the difficulty in registering dynamically the diagnostic information derived from optical parameters with the location from where the optical measurement was taken. Scanning multispectral time-resolved fluorescence spectroscopy (ms-TRFS) [9, 11], for example, has demonstrated ability to rapidly characterize and diagnose diseased tissues based on their autofluorescence properties [12–17]. Nevertheless, this technique, as other optical spectroscopy techniques (i.e.…”
Section: Introductionmentioning
confidence: 99%